Synthesis of γ,δ-Unsaturated Esters and Amides via Au(I)-Catalyzed Reactions of Aryl Ynol Ethers or Ynamides with Allylic Alcohols - Misawa, Souta; Miyairi, Asaki; Oonishi, Yoshihiro; Nolan, Steven P.; Sato, Yoshihiro (Synthesis, 2021)
Polarized alkynes such as ynol ethers and ynamides have attracted much attention due to their inherent unique reactivity. Herein, we report Au(I)-catalyzed hydroalkoxylation/Claisen rearrangement cascade reactions of aryl ynol ethers and ynamides with allylic alcohols. At the first stage (hydroalkoxylation) of this cascade reaction, attack of allylic alcohols to aryl ynol ethers or ynamides occurs at the α-position of the polarized alkynes in a completely regioselective manner. Claisen rearrangement of the resulting adducts subsequently takes place to give γ,δ-unsaturated esters or amides, respectively. The [Au(IPr)NTf2] catalyst is most effective for this reaction, and the reaction proceeds under mild conditions (in the case of aryl ynol ether: in THF, 60 °C; in the case of ynamides: in toluene, 80 °C) in an atom-economical way.
Keywords: gold catalysis; ynols; ynamides; hydroalkoxylation; Claisen rearrangement; esters; amides